АВ=(-8-(-2);-5-(3))=<u>(-6;--8)</u>
(2х+3)² – (х–5)² = 0
(2х)² – 12х + 3² – (х² – 10х + 5²) = 0
4х² – 12х + 9 – (х² – 10х + 25) = 0
4х² – 12х + 9 – х² + 10х – 25 = 0
3х² – 2х – 16 = 0
D = 2² – 4 * 3 * (–16) = 4 + 192 = 196
√D = √196 = 14
x1 = (2 – 14) / 6 = –12 / 6 = – 2
x2 = (2 + 14) / 6 = 16/6 = 8/3 = 2 2/3
Ответ: –2; 2 2/3
Y''=d2y/dx^2=2xy/(x^2+4)
Разделяем переменные
d(dy/y)=(2xdx/(x^2+4))*dx
Интегрируем первый раз
ln(y)*dy=(d(x^2+4)/(x^2+4))*dx
ln(y)*dy=(ln(x^2+4)+lnC1)*dx
Избавляется от логарифмов
y*dy=C1(x^2+4)*dx
Интегрируем второй раз
y=C1(x^3/3+4x)+C2